2018
DOI: 10.32504/hspj.v2i3.41
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan penerapan atraumatic care oleh perawat dengan stres orangtua selama hospitalisasi bayi

Abstract: Hospitalization does not only cause anxiety of the children, but also of the parents. Parental responses to child hospitalization such as: anger, anxiety, insecurity, uncooperative, frustrated and stressful. One of effort to minimize parental stress is the implementation of atraumatic care by nurses. The objective of this study is to know the relationship between the implementation of atraumatic care by nurses with parental stress during the infant’s hospitalization in perinatology ward, Panembahan Senopati Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…18 In contrast, Ulfa et al found a majority of respondents had gained training experiences on atraumatic care that had lowered the stress level of parents. 16 A highly significant positive correlation was found between the knowledge and attitude scores of the respondents regarding atraumatic care and their attitudes. Similarly, the study done by Fiktoria showed a moderate correlation between nurse's knowledge and attitude regarding the application of atraumatic care [26] .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…18 In contrast, Ulfa et al found a majority of respondents had gained training experiences on atraumatic care that had lowered the stress level of parents. 16 A highly significant positive correlation was found between the knowledge and attitude scores of the respondents regarding atraumatic care and their attitudes. Similarly, the study done by Fiktoria showed a moderate correlation between nurse's knowledge and attitude regarding the application of atraumatic care [26] .…”
Section: Discussionmentioning
confidence: 86%
“…13,14,15 Hospitalized children when undergoing a traumatizing event, which if overlooked could psychologically harm and hamper their development which in turn increases the stress in parents and deteriorating their satisfaction with the health care services and atraumatic care is the one that minimizes those detrimental effects. 16,17 With a paucity of studies identifying nurse's level of knowledge and attitude towards the implementation of atraumatic care among hospitalized children in Nepal, this study aimed to identify the level of knowledge and attitude of nurses in the implementation of atraumatic care among hospitalized children in a tertiary level hospital in Eastern Nepal as well as to find the association between different variables considered under the study.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the effect on the parents is anxiety because they are a significant factor in caring for the children during their stay in the hospital. Parents' responses towards their children's hospitalization commonly are disbelief, anger, guilt, fear, anxiety, stress, and frustration (Ulfa et al, 2018;Wong, 2009). Those effects were also stated in Fauziyah's research in a hospital in Bogor regency in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the stress, many aspects will change parents' life by being in the hospital, including daily activities, social and economic issues, and anxiety. By being on their children's side during hospitalization to treat their children's sickness, most parents showed various reactions, including disbelief, anger, guilt, anxiety, frustration and even depression (Ulfa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation